Nonlinear analysis of the plasma wave decay - Khvesyuk, V.I.; Karbushev, D.N. (Вопросы атомной науки и техники, 2009)
Distortions of drift waves form connected with nonlinear processes agreed upon by influence of plasma shear flows
on wave are considered. Plasma velocities are directed along line of wave propagation. It is shown that result of such an
influence is strong transformation of wave. The overturn is achieved. It leads to wave decay. Розглянуто перекривлення форми дрейфових хвиль, пов’язане з нелінійними процесами, які визвано
впливом неоднорідних швидкостей плазми, направленими вздовж лінії розповсюдження хвилі. Показано, що
внаслідок такого впливу хвиля істотно перекривлюється аж до перекидання. Це призводить до розпаду хвилі. Рассматриваются искажения формы дрейфовых волн, связанные с нелинейными процессами, вызываемыми воз-
действием неоднородных скоростей плазмы, направленных вдоль линии распространения волны. Показано, что в ре-
зультате такого воздействия волна существенно искажается, вплоть до опрокидывания. Это ведёт к распаду волны.